Systematic and Comprehensive Analysis of tRNA-Derived Small RNAs Reveals Their Potential Regulatory Roles and Clinical Relevance in Sarcoidosis - Zhao M; Tian C; Di X; Cong S; Cao Y; Zhou X; Wang K (Dove Medical Press, 2023)
Min Zhao, Chang Tian, Xin Di, Shan Cong, Yingshu Cao, Xijia Zhou, Ke Wang Department of Respiratory and Critical Care Medicine, the Second Hospital of Jilin University, Changchun, Jilin, People's Republic of ChinaCorrespondence: Ke Wang, The Second Hospital of Jilin University, No. 218 Ziqiang Road, Nanguan District, Changchun, 130041, People's Republic of China, Email wke@jlu.edu.cnIntroduction: The pathogenesis of sarcoidosis, which involves several systems, is unclear, and its pathological type is non-caseating epithelioid granulomas. tRNA-derived small RNA (tsRNA) is a novel class of short non-coding RNAs with potential regulatory functions. However, whether tsRNA contributes to sarcoidosis pathogenesis remains unclear.Methods: Deep sequencing technology was used to identify alterations in tsRNA relative abundance profiles between patients with sarcoidosis and healthy controls and quantitative real-time polymerase chain reaction (qRT-PCR) was used to validate. The clinical parameters were analysis to evaluate the clinical feature correlations initially. Target prediction and bioinformatics analysis of validated tsRNA were conducted to explore the mechanisms of tsRNAs in sarcoidosis pathogenesis.Results: A total of 360 tsRNAs were identified for exact matches. Among them, the relative abundance of three tRNAs (tiRNA-Glu-TTC-001, tiRNA-Lys-CTT-003, and tRF-Ser-TGA-007) was markedly regulated in sarcoidosis. The levels of various tsRNAs were significantly correlated with age, the number of affected systems, and calcium levels in the blood. Additionally, target prediction and bioinformatics analyses revealed that these tsRNAs may play roles in chemokine, cAMP, cGMP-PKG, retrograde endorphin, and FoxO signalling pathways. The related genes, APP, PRKACB, ARRB2, and NR5A1 finding may participate in the occurrence and development of sarcoidosis through immune inflammation.Conclusion: This study provides novel insights to explore tsRNA as a novel and efficacious pathogenic target of sarcoidosis.Keywords: sarcoidosis, tRNA-derived small RNA, tsRNA, noncoding RNAs, bioinformatics analysis